Effect of temperature, humidity, and crack initiation on properties of PZT micro-actuator. Issue 175 (12th October 2016) - Bintachitt, Patamas; Suaprasert, Puntipa; Aungkavattana, Pavadee
ABSTRACT: PZT has been utilized as micro-actuators to control high positioning accuracy and high-speed data access in high density Hard Disk Drives. The effect of temperature from 25°C to 260°C with humidity (80°C/80% RH) for 120 h on cracked-free and pre-cracked PZT micro-actuators was studied. Both dielectric constant (ϵr ) and piezoelectric coefficient (d31 ) of cracked-free and pre-cracked PZT subjected to humidity remained unchanged. After exposing the cracked-free PZT to temperature above 200°C, both ϵr and d31 were degraded while ϵr and d31 of pre-cracked PZT were degraded at temperature above 180°C and 140°C, respectively. In case of temperature with humidity, the ϵr and d31 were degraded at temperature above 200°C and d31 was dropped by 16% of cracked-free PZT. In case of pre-cracked PZT, both ϵr and d31 were degraded at temperature above 140°C with humidity conditions.